Plan-Based Character Diversity - Coman, Alexandra; Munoz-Avila, Hector (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
Non-player character diversity enriches game environments increasing their replay value. We propose a method for obtaining character behavior diversity based on the diversity of plans enacted by characters, and demonstrate this method in a scenario in which characters have multiple choices. Using case-based planning techniques, we reuse plans for varied character behavior, which simulate different personality traits.